Building an Understanding of the Concept of Heat Through the Implementation of Guided Inquiry Learning with Formative Assessment - Vemita Arielia; Akhmad Jufriadi; Hena Dian Ayu (Universitas Lambung Mangkurat, 2026)
The students' understanding of temperature, heat, and thermal equilibrium remains inadequate, necessitating an educational strategy to enhance their scientific understanding. This study seeks to enhance students' understanding of concepts by employing guided inquiry learning in conjunction with formative assessment on thermal material. The research employed a mixed methods strategy, utilizing quantitative data from concept understanding exams and qualitative data from interviews. Quantitative analysis encompassed descriptive statistics, normalized gain (N-Gain) computations, and independent samples t-tests, and qualitative data was examined through content analysis methodologies. The study's results indicated a significantly greater enhancement in conceptual understanding in the experimental group relative to the control group. The N-Gain value for the experimental group was 0.69 (moderate category), but the control group attained just 0.25 (low category). The data satisfy the statistical requirements, specifically normal distribution (Sig > 0.05) and homogeneity (Sig = 0.406). The t-test results indicated a significant difference between the two courses (t = 73.761; p < 0.001), demonstrating that guided inquiry learning with formative evaluation substantially enhances conceptual understanding. This study's theoretical implications suggest that integrating guided inquiry learning with formative assessment can enhance students' conceptual understanding through scientific investigations and ongoing feedback. The finding corroborates the constructivist approach, which underscores the significance of active learning experiences and cognitive interactions in fostering a more precise and comprehensive conceptual understanding.